The Influence of Work-Life Balance on Happiness at Work Among Nurses - Mumtazah, Imtinan (Psikologi Prima, 2025)
Nurses are an important profession in the demanding medical workforce, making them vulnerable to work pressure, high emotional involvement, and excessive empathy. This pressure can lead to unhappiness at work and the desire to resign. This study aims to examine the effect of work-life balance on happiness at work in nurses. The hypothesis proposed is that there is a positive influence of work-life balance on happiness at work in nurses. This study uses a quantitative approach with the Work-life balance Scale and the SHAW Scale (The Shortened Version of HAW). The number of samples used was 143 nurses working in the DKI Jakarta, West Java, Central Java, East Java, and Banten regions aged over 21 years. With the criteria for length of service for 1 year. The sampling technique used incidental sampling. The data analysis technique was carried out by simple regression with the help of the SPSS program. The results of this study indicate that there is an influence of 27.5% while the remaining 72.5% is influenced by other variables outside the study, which means that the high work-life balance in nurses is positively correlated with the level of happiness at work in nurses, and vice versa.